Linear chains of nanomagnets: engineering the effective magnetic anisotropy. Issue 40 (14th October 2020) - Talapatra, A.; Adeyeye, A. O.
Abstract : Tunable effective magnetic anisotropy is achieved by engineering the thickness and lattice arrangement of linear chains of nanomagnets. Abstract : This paper investigates the control of effective magnetic anisotropy in Permalloy linear chain arrays, achieved by tuning the symmetry arrangement of the ellipsoidal nanomagnets and the film thickness. When the ellipsoidal nanomagnets are coupled along their easy axis, stronger effective magnetic anisotropy is achieved compared to when the nanomagnets are coupled along their hard axis. A clear transition from a single domain state to a combination of complex flux closure states such as a vortex or double vortices is observed at different applied field angles when the film thickness is varied in the range from 20 nm to 100 nm. Tunable microwave absorption spectra, obtained by ferromagnetic resonance spectroscopy, established the complex interplay between the shape anisotropy and magnetostatic interactions, which becomes more intriguing at different film thicknesses and applied field angles. The micromagnetic simulations are in good agreement with the experimental results. Our results demonstrate possible ways of manipulating the effective magnetic anisotropy in arrays of nanomagnets for magnonic and microwave applications.